Evaluation of Bio-efficacy of Calotropis procera Against Juvenile Stage of Common Household Pest Periplaneta americana (American Cockroach) - Shaikh, Kalim; Pathan, Tanvir; Shaikh, Wasim; Shaikh, Rafik (Asian Journal of Biological and Life Sciences)
Aim/Background: The present study aimed to evaluate the effects of Calotropis procera (Aiton) W.T. Aiton against the juvenile stage of common household pest Periplanata americana (American Cockroach). Materials and Methods: The leaf extracts were prepared in selected solvents (methanol, acetone and water) and evaluated against the juvenile cockroaches at different concentrations (10, 20, 30, 40 and 50 ppm). The results of mortality rate were recorded at different time intervals (6, 12, 24 hr) of exposure. Results: The results obtained shows that the methanol extract of plant sample having significant mortality rate at 20 ppm (20.00±8.16%) at 12 hr of exposure. The highest mortality rate of methanol extract was observed at 50 ppm (96.66±3.51%) at 24 hr of exposure. The lowest mortality rate was recorded from acetone extract of 10 ppm (11.66±2.88%) at 24 hr. However, the plant extract shows moderate mortality rate between (12.00±4.35-95.33±4.50%). Conclusion: The present finding reveals that, the mortality rate is in proportion to the concentration level of plant extract and exposure period. Moreover, the results obtained reveals that the plants based biopesticides could be the best alternatives for present synthetic pesticides for controlling the population of cockroaches.
Keywords: Periplanata americana; Calotropis procera; Bioefficacy; Juvenile; Mortality.